1999
DOI: 10.1016/s0306-4522(98)00630-7
|View full text |Cite
|
Sign up to set email alerts
|

Role of apolipoprotein E and estrogen in mossy fiber sprouting in hippocampal slice cultures

Abstract: Abstract-A role for apolipoprotein E is implicated in regeneration of synaptic circuitry after neural injury. The in vitro mouse organotypic hippocampal slice culture system shows Timm's stained mossy fiber sprouting into the dentate gyrus molecular layer in response to deafferentation of the entorhinal cortex. We show that cultures derived from apolipoprotein E knockout mice are defective in this sprouting response; specifically, they show no sprouting in the dorsal region of the dentate gyrus, yet retain spr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(45 citation statements)
references
References 77 publications
(82 reference statements)
3
42
0
Order By: Relevance
“…This concentration of E 2 also induces maximal apoE induction in mixed glia [195]. E 2 -dependent sprouting can be blocked by P 4 or tamoxifen [192]. P 4 appears to differ from MPA in its ability to regulate synaptic plasticity.…”
Section: Progesterone Regulation Of Glial Cell Function and Responsementioning
confidence: 85%
See 2 more Smart Citations
“…This concentration of E 2 also induces maximal apoE induction in mixed glia [195]. E 2 -dependent sprouting can be blocked by P 4 or tamoxifen [192]. P 4 appears to differ from MPA in its ability to regulate synaptic plasticity.…”
Section: Progesterone Regulation Of Glial Cell Function and Responsementioning
confidence: 85%
“…During pregnancy, two-fold increases in uterine apoE levels are associated with increased import of maternal lipids [190]. Also, estrogen-dependent sprouting of perforant path fibers to the hippocampus is absent in apoE-knockout mice [191] [189] [192]. Complex heterotypic cellular interactions that occur in response to ovarian steroids extend beyond astrocytic-neuronal interactions.…”
Section: Progesterone Regulation Of Glial Cell Function and Responsementioning
confidence: 99%
See 1 more Smart Citation
“…In the absence of ApoE, estrogen did not show any effect on neurite sprouting (42,43). Nathan et al (16) found that E 2 -induced neurite sprouting depended on the ApoE genotype.…”
Section: E2-regulated Apoe Expression Is Mediated By Er and Is Er Isomentioning
confidence: 98%
“…In previous work, 50 the authors found that axonal sprouting was stimulated by estrogen through upregulation of apolipoprotein E expression, but progesterone inhibited this effect. In contrast, other steroids, such as prednisolone, inhibit aberrant sprouting in the injured rat spinal cord.…”
Section: Discussionmentioning
confidence: 91%